Visible-light photodegradation of nitrobenzene by microwave synthesized ZnO and its nanocomposites Ag/ZnO and Cu/ZnO - Sidi, Hauwa Aliyu (2014)
ZnO and Ag/ZnO was successfully synthesized using the microwave extraction irradiation at low temperature of 90oC and power of 120 Watt while Cu/ZnO was produced at 240 Watt after 15 minutes. The synthesized nanopowders were characterized by X-ray diffraction (XRD), Transmission electron microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM) and X-ray Fluorescence (XRF). The band gaps energy of the nanocomposites were from absorption data obtained from UVVis- NIR spectroscopy. All the samples indicated the synthesized nanocomposites showed hexagonal ZnO structure. The average crystallite sizes of the composites estimated using Scherrer’s equation was found to be less than 100 nm which is smaller than the actual particle sizes in the images obtained from transmission electron microscopy (TEM) analysis which were found to be below 200 nm with rod-like particle and this is true since in the actual sense crystallite size are expected to be small than particle size because it is group of crystallite particles that composes the crystalline material forming particle. The elemental composition of the samples were confirmed through EDX and XRF analysis. The photodegradation efficiency of the synthesized nanocomposites was evaluated by employing nitrobenzene as a model organic pollutant. Adsorption study was carried out in order to establish the adsorption-desorption equilibrium. And the maximum adsorption time was found to be 45 minutes with maximum catalyst load of 0.25 g for ZnO and Cu/ZnO and 0.5 g for Ag/ZnO. The efficiency of all the MW-synthesized nanocomposites was found to be higher than the commercial ZnO. Ag/ZnO was found to have the highest efficiency of 96.47% after 2 hours of photodegradation and adsorption process.